Analysing drivers of vulnerability to flooding: a systems approach. Issue 1 (2nd January 2019) - Mavhura, Emmanuel
ABSTRACT: Vulnerability to disasters is both dynamic and context-specific. Understanding the construction of vulnerability to disasters is important because the survival of communities is threatened. However, many vulnerability drivers are often hidden and remote from the triggering events; as such, they need to be analysed using approaches that unpack the non-linear interactions. A systems-thinking approach to examine the construction of vulnerability to flood disasters in Muzarabani district, Zimbabwe is used. Data was gathered from interviews, workshops, field observations and the 2012 census report. Biophysical vulnerability is driven by interacting factors including proximity to low-lying floodplain, interfluves and cyclonic path; flood recession agriculture; heavy erosion and siltation; and use of poor quality materials. Social vulnerability to flooding is propelled by a bundle of demographic and poor socio-economic conditions of the community that make the smallholder farmers succumb to flood impacts. None of those variables make the community vulnerable on its own. Rather, they are mutually inclusive, with each one reinforcing the other(s). Vulnerability to flooding in Muzarabani is thus not solely a function of changes in the rainfall pattern to which communities respond. Rather, it is a result of multiple interdependent physical and poor socio-economic variables involving non-linear relationships.